2015
DOI: 10.1124/dmd.115.065292
|View full text |Cite
|
Sign up to set email alerts
|

The Nonspecific Binding of Tyrosine Kinase Inhibitors to Human Liver Microsomes

Abstract: Drugs and other chemicals frequently bind nonspecifically to the constituents of an in vitro incubation mixture, particularly the enzyme source [e.g., human liver microsomes (HLM)]. Correction for nonspecific binding (NSB) is essential for the accurate calculation of the kinetic parameters K m , Cl int , and K i . Many tyrosine kinase inhibitors (TKIs) are lipophilic organic bases that are nonionized at physiologic pH. Attempts to measure the NSB of several TKIs to HLM by equilibrium dialysis proved unsuccessf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…At the end of the incubation period, a 25-ml aliquot of the mixture from each of the buffer and the sample chamber was mixed with 475 ml of ice-cold acetonitrile containing 50 nM tolbutamide (internal standard; final concentration of 47.5 nM in 500 ml final volume). Control protein binding experiment was performed on human liver microsomes (100 mg) with drugs known to be highly bound to microsomal or plasma proteins; i.e., gefitinib (1 mM) (Burns et al, 2015) and abiraterone (1 mM). (Marbury et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the incubation period, a 25-ml aliquot of the mixture from each of the buffer and the sample chamber was mixed with 475 ml of ice-cold acetonitrile containing 50 nM tolbutamide (internal standard; final concentration of 47.5 nM in 500 ml final volume). Control protein binding experiment was performed on human liver microsomes (100 mg) with drugs known to be highly bound to microsomal or plasma proteins; i.e., gefitinib (1 mM) (Burns et al, 2015) and abiraterone (1 mM). (Marbury et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…It is clear, however, that physicochemical and chemical properties other than charge and lipophilicity determine NSB and hence fu mic . For example, we and others have reported that molecular mass, polar surface area, charge distribution, the number of hydrogen bond donors/ acceptors, and the presence of halogen atoms (especially the trifluoromethyl group) may all influence NSB (Gao et al, 2008;Li et al, 2009;McLure et al, 2011;Burns et al, 2015). Moreover, we demonstrated recently that algorithms commonly used to calculate logP gave widely discrepant values of this parameter, differing by as much as a factor of 2 (i.e., 2 log units) (Burns et al, 2015).…”
Section: Introductionmentioning
confidence: 75%
“…However, both techniques are time-consuming, requiring measurement of the drug concentration in each compartment of the dialysis apparatus or, in the case of ultrafiltration, in the reservoir and filtrate. Solubility is also a problem for highly lipophilic compounds (Burns et al, 2015). Given the broad dependence of NSB on lipophilicity and charge state, several algorithms based on these properties have been developed to predict fu mic , thereby circumventing the need for experimental methods (Austin et al, 2002;Hallifax and Houston, 2006;Sykes et al, 2006;SimCYP calculator).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Robust determination of in vitro dabrafenib transporter kinetics is precluded by limited aqueous solubility, which confounds assessment of compartmentalized drug concentrations in systems such as trans-well-based transporter assays. 25 In the absence of robust in vitro data, intestinal and hepatic transporter (transporter-mediated intrinsic clearance; CL intT ) and diffusion (passive diffusion clearance; CL PD ) kinetics were determined using the parameter estimation (PE) function in Simcyp. 26 Parameter estimations were based on in vivo data from a phase I single-dose escalation trial (GSK trial ID: 112680) involving 94 melanoma patients over six dose levels (37.5-300 mg).…”
Section: Development and Verification Of The Dabrafenib Pbpk Modelmentioning
confidence: 99%